2020
DOI: 10.3389/fgene.2020.552444
|View full text |Cite
|
Sign up to set email alerts
|

Terminus-Associated Non-coding RNAs: Trash or Treasure?

Abstract: 3 untranslated regions (3 UTRs) of protein-coding genes are well known for their important roles in determining the fate of mRNAs in diverse processes, including trafficking, stabilization, translation, and RNA-protein interactions. However, non-coding RNAs (ncRNAs) scattered around 3 termini of the protein-coding genes, here referred to as terminus-associated non-coding RNAs (TANRs), have not attracted wide attention in RNA research. Indeed, whether TANRs are transcriptional noise, degraded mRNA products, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…Two studies published simultaneously in Nature in 2013 revealed that circRNA acts as a microRNA (miRNA) molecular sponge (7,8) and that circRNAs can bind to miRNAs in a sequence-specific manner. miRNAs play a crucial role in the regulation of gene expression and cell function (9), including in tumor metabolism which has been widely reported. miRNAs bind to the 3'-untranslated region (3'-UTR) of mRNA to degrade the target gene or inhibit its protein translation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies published simultaneously in Nature in 2013 revealed that circRNA acts as a microRNA (miRNA) molecular sponge (7,8) and that circRNAs can bind to miRNAs in a sequence-specific manner. miRNAs play a crucial role in the regulation of gene expression and cell function (9), including in tumor metabolism which has been widely reported. miRNAs bind to the 3'-untranslated region (3'-UTR) of mRNA to degrade the target gene or inhibit its protein translation (10,11).…”
Section: Introductionmentioning
confidence: 99%